Analysis of Educational Quality for People on the Autism Spectrum: A Review of the Literature - Piedra, Dina Marisol Calonge De La; Zamudio, Rivera; Davila, Yvette Vanessa Criado; Urbano, Virginia Asuncion Cerafín; Hidalgo, Cinthya Virginia Soto (Indian Journal of Information Sources and Services, 2025)
The objective of this research was to determine, through a review of the literature, the perception of parents of children with autism spectrum disorder on the quality of education for people with this disorder in Lambayeque. The research was of a mixed type. A sample of 80 parents was considered. For data collection, a previous interview was carried out, followed by the application of a questionnaire. The results indicate that 48% of the sample disagreed on the correct implementation of early intervention programs; 54% of the participants disagreed on whether it is easy for their child to attend school. Fifty-eight percent of the sample totally disagreed on whether teachers are trained to attend to children with ASD at school. Finally, a negative perception of the is evident, since they indicated that they totally disagree with the process of quality and accessibility to education, programs, etc. for children with ASD.